Cardiovagal modulation in pediatric functional gastrointestinal disorders. Issue 5 (27th March 2019) - Chelimsky, Gisela; Rausch, Sydnee; Bierer, Douglas; Feng, Mingen; Simpson, Pippa; Awe, Elizabeth; Chelimsky, Thomas
Abstract: Background and Objectives: Though reduced cardiovagal modulation accompanies adult IBS, adolescents with functional gastrointestinal disorders (FGID) have not been studied. We aim to investigate whether adolescents with FGID have reduced cardiovagal modulation. Methods: After 10‐minute supine rest, we recorded ECG for 5‐minute supine and 5‐minute standing without support in healthy and FGID‐affected adolescents. After analysis with Kubios 2.2 for high‐frequency (hf) and low‐frequency (lf) heart rate variability (HRV), Wilcoxon signed‐ranks test compared individual paired supine and standing HRV data, while Kruskal‐Wallis and Mann‐Whitney U tests compared HRV across groups. Results: A total of 50 FGID subjects (90% females; median age 17 years [range 11‐21]) and 22 healthy comparison group (HC) (59% females; median age 14 years [range 10‐18]) participated. Both absolute and relative supine hfHRV exceeded standing in both groups. Absolute supine lfHRV was higher than standing in FGID patients and not in HCs, while relative supine lfHRV power was actually lower in both groups. Compared to HC, FGID group showed significantly lower absolute HRV, while relative HRV did not differ between groups. Conclusions: Cardiovagal modulation is lower in adolescents with FGID. This difference impacts these subjects significantly. Whether this finding reflects a cause or a consequence of FGID is unknown. Abstract : Cardiovagal modulation measured through heart rate variability is lower in adolescents with FGID. This difference impacts these subjects significantly.